PENGARUH LITERASI KEUANGAN DAN TOLERANSI RESIKO TERHADAP KEPUTUSAN INVESTASI SAHAM PADA APLIKASI STOCKBIT (STUDI KASUS GENERASI Z DI DKI JAKARTA) - Taria, Putri Anas; Purwaningrum, Endang; Mirati, R Elly (Yayasan Education and Social Center, 2025)
The increasing number of capital market players, the majority of whom are members of Generation Z in DKI Jakarta, is not always accompanied by adequate financial understanding and risk awareness. This situation is a challenge in producing logical investment decisions, especially with the emergence of digital investment platforms such as the Stockbit application. The purpose of this study is to gather empirical data regarding how Risk Tolerance and Financial Literacy affect Generation Z stock investment choices in DKI Jakarta who utilise the Stockbit app. IBM SPSS version 22 software is used to analyse multiple linear regression analysis in this quantitative investigation. The sampling method used is purposive sampling of 100 Generation Z respondents who live in DKI Jakarta and have invested through the Stockbit application. The research findings show that financial literacy and risk tolerance, both separately and simultaneously, have a positive and significant influence on stock investment decisions. This underscores the importance of understanding finance and readiness to face risk as key factors in making intelligent investment decisions in the digital era.